Training Educators to Foster Inclusion and Resilience: Lessons From Ukraine - Sergiy Sydoriv (Vasyl Stefanyk Precarpathian National University, 2023)
The implementation and development of inclusive education are one of the goals of Ukraine's educational reform, thus training and professional development of teachers involves building skills to teach students with special educational needs and disabilities in inclusive settings. Over the past five years, there has been a significant increase in the enrollment numbers of students with special educational needs, so the quality training of educators with the understanding and capacity to organize a safe and inclusive learning environment should be a priority of education policy. The paper analyses the consequences of the military invasion of the Russian Federation and the humanitarian crisis it caused that deteriorate and disrupt educational services for all categories of students, including those with disabilities. Still, notwithstanding air raids, targeting civilian infrastructure, war crimes, violations of basic human rights, and forced migration, the Ukrainian state and its educational system display signs of resilience. It is highlighted that being a result and a process of positive adaptation to adverse circumstances, resilience should be studied in the context of resistance and vitality of Ukrainian society during the war and post-war recovery. It is found that diverse reactions to stressful and traumatizing factors can be determined and caused by multiple dynamic interactions at the personal and systemic levels. Psychological resilience as the ability to resist a traumatic impact may vary individually; however, it can be effectively developed within the socio-ecological system framework. Its application involves understanding that the development is influenced by a combination of interactions at the micro-, meso-, exo-, macro-, and chrono-system levels. Thus, teacher training in universities and colleges, being conducted at the organizational system level, can build individual resilience and, consequently develop community, society, national and global resilience at the present and in the future. It is emphasized that developed individual resilience can eliminate the appearance of behavioral and mental disorders (ADHD, PTSD, anxiety syndrome, deviant behavior) in children and social marginalization, aggression, and mental disorders in adults who were exposed to traumatic war events. Thus, it is important to analyze resilience at all levels during the acute phase of the conflict and to develop mechanisms for the development of individual and national resilience in the post-war period. The paper presents the findings of the inclusion and resilience awareness survey among pre-service teachers. The hypothesis has been proposed that the application of inclusive practices contributes to building resilience and enforces national resistance to aggression. The author substantiates the introduction of narrative speech, art and performance techniques, inclusive community leadership, and building soft skills in the professional training of educators. The ideas and practices of including persons with disabilities, veterans and those affected by the war should be applied while developing models of assessment, monitoring, and building resilience. Thus, teacher training can provide invaluable resources for an inclusive and resilient society.